Postmenopausal hormone therapy and its association with breast cancer - Arshi Syal; Neelam Aggarwal (Wolters Kluwer Medknow Publications, 2020)
With the cessation of estrogen and progesterone at menopause, the hormone withdrawal affects various systems in the woman's body. In earlier days, menopausal hormone therapy (HT) was prescribed for primary prevention of coronary artery disease (CAD) and osteoporosis, which were thought to be because of estrogen deprivation and epidemiologic data supported a beneficial effect of estrogen on the heart and bone. Later on, robust data from the Women's Health Initiative study comparing two HT trials demonstrated adverse outcomes in terms of excess risk of CAD, stroke, venous thromboembolism, and breast cancer. Even with risk stratification based on family history, approximately only 15% of women diagnosed with breast cancer have such a risk factor. This implies that family history will not be elicited in more than 85% of women who develop breast cancer. Literature review suggests that the prior use of conjugated equine estrogen (CEE) alone has the potential to be effective as an intervention, leading to a reduction in mortality due to breast cancer. Therefore, it is time to reevaluate the risk reduction strategies for breast cancer that are currently in practice. In terms of absolute numbers, for every 10,000 person-years of prior use of CEE alone, there would be only two fewer deaths from breast cancer and two fewer deaths secondary to its sequelae. This translates into a significant number of women in our country with a population of 1.38 billion (of which 48%, nearly 650 million, are women).